System study of pneumatic exoskeleton rehabilitation manipulator. Issue 13 (21st November 2018) - Ma, Xudong; Yuan, Ruibo; Fang, Sizhong
Abstract : In this study, biological characteristic of manpower is analysed and then the structural of exoskeleton rehabilitation manipulator is designed base on the thought of modular. First, the overall assembly drawing is drawn by SolidWorks. Second, the controlled pneumatic system is designed. The mainly contents are selecting mini pneumatic cylinder as a driver and controlling electromagnetic reversing valve which can lead to the piston movement of cylinder by STM32F429 microcontroller. At last, the movement simulation of exoskeleton rehabilitation manipulator is done and analysed by ADAMS, and then the experimental research of the same move pattern with simulation is carried out. It is proved that the pneumatic exoskeleton rehabilitation manipulator system has certain reliability and feasibility. Furthermore, it has the ability to meet the rehabilitation needs of patients with finger movement disorders.